2020
DOI: 10.3390/ijerph17238818
|View full text |Cite
|
Sign up to set email alerts
|

The Retail Food Sector and Indigenous Peoples in High-Income Countries: A Systematic Scoping Review

Abstract: Indigenous Peoples in high-income countries experience higher burdens of food insecurity, obesity, and diet-related health conditions compared to national averages. The objective of this systematic scoping review is to synthesize information from the published literature on the methods/approaches, findings, and scope for research and interventions on the retail food sector servicing Indigenous Peoples in high-income countries. A structured literature search in two major international databases yielded 139 rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 205 publications
(383 reference statements)
1
12
0
Order By: Relevance
“…Yet rather than suggesting that food environments are therefore unimportant, we advocate for models that recognize the complexity of social behavior and how political, economic, and cultural contexts shape dietary practices. This research contributes to the small number of studies on the retail food environments of Indigenous people [39,40]. In line with past research, we found significant barriers to accessing nutritious foods, particularly within the more rural communities [58][59][60]65].…”
Section: Discussionsupporting
confidence: 85%
“…Yet rather than suggesting that food environments are therefore unimportant, we advocate for models that recognize the complexity of social behavior and how political, economic, and cultural contexts shape dietary practices. This research contributes to the small number of studies on the retail food environments of Indigenous people [39,40]. In line with past research, we found significant barriers to accessing nutritious foods, particularly within the more rural communities [58][59][60]65].…”
Section: Discussionsupporting
confidence: 85%
“…Indigenous populations throughout the world have been stripped of their resources with many Indigenous people living in areas that are classified as 'food deserts' [13]. Indigenous populations are more likely to be food insecure compared to the general population of their country [14][15][16]. Urban Indigenous people face even greater food insecurity compared to rural Indigenous populations [15].…”
Section: Accessmentioning
confidence: 99%
“…To address the healthy food access issue in communities, it is necessary understanding the role of the local retail food environment in enabling or hindering resource-poor community residents’ access to healthy food for making better food choices. Past reviews conducted on the food environment have focused on associations between school food environments and children’s diet 29 30 child weight status, 31 food environment in high-income countries 32 and low-income and middle-income countries. 25 The majority of literature to date has also focused on the food environment and overweight/obesity and physical activity and not given much attention to dietary outcomes more especially food choices.…”
Section: Study Rationalementioning
confidence: 99%